(untitled) (Bangladesh Journal of Zoology, 2021)
Copy’s frog, commonly observed in Bangladesh, is ecologically important for evergreen forest. Sample was collected from Satchari National park, Hobigonj, Sylhet. Attempts were made to combine morphological and molecular techniques for identification and analysis of evolutionary relation of Copy’s frog with anuran species. Morphological identification of Hydrophylax sp. was conducted based on distinguishing characteristics of the body and different body measurement parameter. The species was identified morphologically as Hydrophylax leptoglossa based on the taxonomic key of finger toes and formula was 3>1>4>2. Simultaneously genomic DNA was isolated using CTAB extraction method. The 16S rRNA gene was amplified from the genomic DNA by polymerase chain reaction method using the pair of universal primers. Amplified product was a 308 bp fragment that generated AT/GC ratio of 1.08% once sequenced. In the present study comparative analysis of intraspecific and interspecific variation was conducted based on nucleotide sequence of 16S rRNA gene collected from GenBank. The intraspecific variation compares between Southeast Asia and Bangladesh was 1.29% for 16S rRNA gene. The interspecific genetic divergence was studied between H. leptoglossa and H. tytleri was observed 14.29%. The nucleotide sequence of the present study will be used as DNA barcode for that particular individual collected from Sylhet, Bangladesh. Furthermore, a molecular phylogenetic tree was constructed, where all the anuran species from a monophyletic group. Four species of Hydrophylax form monophyletic group and is consistent with relation based on morphology. Bangladesh J. Zool. 49(1): 105-115, 2021